PENERAPAN STRATEGI DELIVERY YANG BEROREANTASI PADA TUJUAN UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN PKn SISWA KELAS V SDN 009 AIR EMAS KECAMATAN UKUI - Santika Juwito (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low result of fifth grade students learn civics SDN 009 AirEmas, poor learning outcomes is caused by out of 30 students only 15 students who completedand the average value of 45.50 students. Therefore, researchers conducted a study with thegoal of improving student learning outcomes Civics by implementing strategies thatberoerientasi delivery at destination. This research is a class act, carried out by two cycles.The data used in this study is the activity data and the teacher and student learning outcomesCivics. Based on the research that has been done, the result for Civic Education learningoutcomes of students has peningkata on each cycle. It is characterized by: (a) the activities ofteachers has increased in each cycle, the first cycle of meetings I gained a score of 6(37.50%), in the first cycle II meeting increased with a score of 8 (50.00%), the second cyclemeeting I rose with a score of 10 (62.50%). And the second cycle II meeting increased with ascore of 14 (87.50%). Besides the student activity increased in the first cycle of the firstmeeting of student activity obtained a score of 9 (56.25%), in the first cycle II meetingincreased with a score of 10 (62.50%), the second cycle of the first meeting increased with ascore of 12 (75 , 00%). And the second cycle II meeting increased with a score of 15(93.75%); and (b) Complete and Civics learning outcomes of students has peningakatan oneach cycle. At the base score is the number of students who completed 15 students (50.00%)with an average value of 45.50. In the first cycle the number of students who pass increaseswith the number of 25 students (83.00%) with an average value of 76.50. And the secondcycle the number of students who pass the increases with the number of 28 students (93.00%)with an average acquisition value of 82.25.